Computers [1999 technology forecast and analysis]. - Dutta-Roya, A. (IEEE spectrum)
This paper presents a computer technology analysis and forecast for 1999. The subjects covered include personal computers, magnetic disk storage, open operating systems, digital versatile disks and supercomputers